Удосконалення інструментарію оцінки та аналізу підприємницької діяльності туристичного підприємства - Сергієнко, Олена Андріанівна; Баранова, Валерія Вадимівна; Шеянова, Еліна Дмитрівна (My University, 2019)
Робота присвячена розробленню комплексного інструментарію удосконалення підприємницької діяльності туристичного підприємства, впровадження якого дасть змогу оцінити рівень конкурентоспроможності підприємства; спрогнозувати попит на послуги туристичної фірми; визначити суттєві фактори впливу на попит туристичної фірми; визначити групи споживачів та обрати цільові сегменти ринку; розробити комплекс рекомендацій щодо вибору підприємницької стратегії туристичного маркетингу. Результати дослідження можуть бути використані на рівні крупних, середніх та малих підприємств. Завдяки розробленому інструментарію туристичне підприємство отримає обґрунтовану оцінку розпізнавання класу клієнта, що дасть змогу пропонувати залежно від ситуації розроблені саме для нього туристичні тури та можливі знижки й акції. Виходячи з проведеного дослідження та реалізації запропонованого інструментарію, скоригована головна мета розвитку рівня підприємництва туристичного підприємства з урахуванням сучасних умов, що полягає у збільшенні частки ринку та покращенні своєї позиції відносно головних конкурентів. Результати можуть бути впроваджені для вдосконалення маркетингової стратегії та розвитку туристичного підприємства.

The goal of the work is to develop a comprehensive toolkit for the improvement of an entrepreneurial activity of a tourist company, which allows to estimate the level of competitiveness of a company; to predict the demand for services of a tourist firm; to identify the significant factors affecting the demand of a tourist firm; to identify consumer groups and select target market segments; to develop a complex recommendations on choosing a business strategy for tourism marketing. The proposed comprehensive research toolkit is aimed at improving the level of competitiveness by evaluating and analyzing the external factors of a tourist company (demand formation, identification of the target segment), and internal environment (financial flows, net income formation). In the study are presented the evaluation of the factors of the company's competitive position; assessment and analysis of factors. It affect the formation of sales and building a dependency model, between these factors and the volume of sales; researches aimed at the allocation of the target segment of consumers, and establishing the relationship between the individual characteristics of consumers and the frequency of travel in Ukraine and abroad. Estimation of the internal environment allows to estimate a financial condition of a tourist company, financial opportunities relative to competitors in the development of entrepreneurship in the tourism industry. Due to the developed toolkit the tourist company will receive the reasonable estimation of the recognition of the client class, which will allow to offer him (her), depending on the situation, special tourist tours and possible discounts and promotions. The conducted factor analysis of the external environment proves that currently tourist companies are in an unfavorable external environment. The level of competitiveness of the investigated company is assessed as a strong one, therefore it is suggested to choose a strategy that takes into account the capabilities of the company and threats of the external environment and is consistent with such corporate strategies as "Limited growth" and "Accelerated growth".
Tools improvement for assessment and analysis of entrepreneurial activity of a tourist company
Keywords: підприємництво; туризм; туристична фірма; конкурентоспроможність; споживачі; маркетинг; сегментація; стратегія; entrepreneurship; tourism; travel agency; competitiveness; consumers; marketing; segmentation; strategy